2014
DOI: 10.15252/embj.201488456
|View full text |Cite
|
Sign up to set email alerts
|

Akirin specifies NF ‐κB selectivity of Drosophila innate immune response via chromatin remodeling

Abstract: The network of NF-κB-dependent transcription that activates both pro- and anti-inflammatory genes in mammals is still unclear. As NF-κB factors are evolutionarily conserved, we used Drosophila to understand this network. The NF-κB transcription factor Relish activates effector gene expression following Gram-negative bacterial immune challenge. Here, we show, using a genome-wide approach, that the conserved nuclear protein Akirin is a NF-κB co-factor required for the activation of a subset of Relish-dependent g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
128
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(138 citation statements)
references
References 58 publications
8
128
1
1
Order By: Relevance
“…Recently, Bonnay et al showed that Drosophila Bap60 interacts with Akirin upon immune challenge, and Bap60-Akirin complex is required for the induction of a subset of IMD target genes, indicating that Bap60 acts as a positive regulator for IMD-pathway42, and is consistent with our result obtained using the inducible Bap60 RNAi flies (Fig. 2D).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Bonnay et al showed that Drosophila Bap60 interacts with Akirin upon immune challenge, and Bap60-Akirin complex is required for the induction of a subset of IMD target genes, indicating that Bap60 acts as a positive regulator for IMD-pathway42, and is consistent with our result obtained using the inducible Bap60 RNAi flies (Fig. 2D).…”
Section: Discussionsupporting
confidence: 91%
“…Another deubiquitinase, CYLD (for Cylindromatosis), modulates the IKK complex to control Relish phosphorylation (Tsichritzis et al, 2007). POSH controls the complex of TAK1 and TAB2; an SCF complex of S kp1, C ullin and F -box protein regulates the phosphorylated Relish-N; Akirin and Relish-N co-regulate some target genes of the Imd pathway (Tsuda et al, 2005; Cardozo and Pagano, 2004; Bonnay et al, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, akirins participate in regulating gene expressions in numerous physiological processes, including the innate immune responses of mammalians and insects (Goto et al, 2008;Tartey et al, 2014), metazoan myogenesis (Marshall et al, 2008;Salerno et al, 2009), mammalian carcinogenesis (Komiya et al, 2008), insect reproduction, and arthropod growth (Almazán et al, 2005;de la Fuente et al, 2006de la Fuente et al, , 2008. Furthermore, the study demonstrated that akirins are required to activate a subset of Relish-dependent genes (Bonnay et al, 2014). Akirins acted in concert with relish (rel) protein in the NFkB dependent signaling pathway, which induces the expression of a subset of downstream pathway elements (e.g., LEAP-1 and LEAP-2) (Goto et al, 2008;Hou et al, 2013;Xue et al, 2014).…”
Section: Introductionmentioning
confidence: 96%